Colicine production as an epidemiological marker for Shigella sonnei. - Vlajinac, H. (Cambridge University Press, 1983)
The reliability of colicine typing of Shigella sonnei: as an epidemiological marker has been investigated. Strains from 13 of 110 excretors showed variation in type as determined by typing serial isolates and in 14 of 106 epidemics there was a lack of uniformity in typing results. The simultaneous presence of two types was found in 11.4% of patients. In vitro variation was seen after 10 days in 6.8% of isolates from 44 stools; variation had risen to 9% when isolates were re-examined after one month. These results suggest that restrictions should be placed on the use of colicine typing as an epidemiologic tool.